Orthodontic-orthognathic interventions in orthognathic surgical cases: "Paper surgery" and "model surgery" concepts in surgical orthodontics - Narayan H Gandedkar; Chai Kiat Chng; Vincent Kok Leng Yeow (Contemporary Clinical Dentistry, 2016)
Thorough planning and execution is the key for successful treatment of dentofacial deformity involving surgical orthodontics. Presurgical planning (paper surgery and model surgery) are the most essential prerequisites of orthognathic surgery, and orthodontist is the one who carries out this procedure by evaluating diagnostic aids such as crucial clinical findings and radiographic assessments. However, literature pertaining to step-by-step orthognathic surgical guidelines is limited. Hence, this article makes an attempt to provide an insight and nuances involved in the planning and execution. The diagnostic information revealed from clinical findings and radiographic assessments is integrated in the "paper surgery" to establish "surgical-plan." Furthermore, the "paper surgery" is emulated in "model surgery" such that surgical bite-wafers are created, which aid surgeon to preview the final outcome and make surgical movements that are deemed essential for the desired skeletal and dental outcomes. Skeletal complexities are corrected by performing "paper surgery" and an occlusion is set up during "model surgery" for the fabrication of surgical bite-wafers. Further, orthodontics is carried out for the proper settling and finishing of occlusion. Article describes the nuances involved in the treatment of Class III skeletal deformity individuals treated with orthognathic surgical approach and illustrates orthodontic-orthognathic step-by-step procedures from "treatment planning" to "execution" for successful management of aforementioned dentofacial deformity.